Practical Tajwid Mentoring to Improve the Quality of Qur’anic Recitation among TPA Children at As-Syafi’iyah Musholla, Tempursari Village, Taman Hamlet - Faidur Robbani; Zainul Arifin; Badria Badria (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The ability to recite the Qur’an in accordance with the rules of tajwid is a fundamental religious skill that should be developed from an early age. Preliminary observations at TPA Mushollah As-Syafi’iyah, Taman Hamlet, Tempursari Village, indicated that several students experienced difficulties in applying tajwid rules, pronouncing Arabic letters according to their proper makhraj, and reciting the Qur’an fluently and accurately. Therefore, this community service program aimed to improve the quality of Qur’anic recitation through a practical tajwid mentoring program. The participants consisted of 15 students of TPA Mushollah As-Syafi’iyah. The program was conducted from January to February 2026 using the Participatory Action Research (PAR) method, which actively involved participants in the stages of needs identification, planning, action implementation, observation, and reflection. The intervention included instruction in basic tajwid, makhraj exercises, practice of Qur’anic recitation rules, the talaqqi method, and intensive Qur’anic reading assistance. The results demonstrated improvements in the students’ understanding of tajwid principles and their ability to recite the Qur’an more accurately, fluently, and in accordance with proper recitation rules. Furthermore, the participants showed high levels of enthusiasm and active participation throughout the mentoring process. Therefore, the PAR-based practical tajwid mentoring program proved effective in enhancing the quality of Qur’anic recitation and contributed positively to strengthening religious education within the community.